Media Production; Revolution Production: How Revolutionary has Tunisian Media Become After The 2011 Uprising ? - محمد بن عبد الوهاب احمد (المجلة المغربية للبحث في العلوم الإنسانية والاجتماعية)
Arab media has been a tool for authoritarian autocratic political systems aiming to disseminate state interests and ensure regime survival. Tunisian media was no exception. All news outlets were a means to praise governmental policies and control liberties. The collapse of Ben Ali’s regime in early 2011 was an opportunity to build a new mediascape: free, independent and reliable. This paper is a pondering on the interrelation between media and politics and on whether the revolutionary uprising in Tunisia has generated a similar revolution in Tunisian media. Special attention is paid to